PERAN KONSELING MULTIKULTURAL DALAM MENINGKATKAN KOMUNIKASI LINTAS BUDAYA SISWA DI SMP 8 SAROLANGUN - Miftahul Rahmah; Dina Hajja Ristianti; Hendra Harmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Multicultural counseling plays a role in improving students' communication skills. Through counseling sessions, students are taught how to communicate effectively and sensitively to other cultures which in turn can reduce misunderstandings and increase collaboration among them. With these skills, students can not only interact better in the classroom, but also outside the school environment, preparing them to face an increasingly connected world. In this study, researchers used qualitative research while for the research location, researchers chose SMP 8 Sarilangun. The results of multicultural counseling research in junior high schools not only serve to improve cross-cultural communication, but also to form a generation that is more tolerant, empathetic, and ready to face a diverse world. The implementation of this strategy in schools will create a more inclusive and harmonious learning environment for all students. Multicultural counseling serves as an effective tool to improve cross-cultural communication among students. By facilitating understanding, improving communication skills, building social networks, and overcoming stereotypes, it contributes to the creation of a more inclusive and harmonious learning environment.